The Implementation of Problem Based Learning to Students Learning Outcomes in Learning Islamic Religious Education at SMPN 7 Palu - Zahratunnisa, Aisyah; Askar, Askar; Zuhra, Zuhra; Nursyam, Nursyam (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2025)
The choice of learning model has an impact on the results achieved. The aim of this research was to find out how Problem Based Learning (PBL) was implemented and how was the implications of implementing Problem Based Learning on students’ learning outcomes in learning Islamic Religious Education at class VIII PAI learning at SMPN 7 Palu. The approach used qualitative descriptive method, by using observation, interview and documentation. The sample of this research was the Eighth-grade students at SMPN 7 Palu. The result showed that the implementation of the Problem Based Learning in learning Islamic religious education at SMPN 7 Palu has been running well. After applying the PBL method, the students feel more interested in learning Islamic religious education. They were challenged in solving the problems they have because they were feeling enthusiastic and interested in learning.